Allergic multimorbidity of asthma, rhinitis and eczema over 20 years in the German birth cohort MAS. Issue 5 (August 2015) - Gough, Hannah; Grabenhenrich, Linus; Reich, Andreas; Eckers, Nora; Nitsche, Oliver; Schramm, Dirk; Beschorner, John; Hoffmann, Ute; Schuster, Antje; Bauer, Carl‐Peter; Forster, Johannes; Zepp, Fred; et al.
Abstract Background The occurrence of allergic multimorbidity (coexistence of asthma, allergic rhinitis and eczema) has not been evaluated longitudinally from early childhood up to adulthood in a population‐based study sample. We aimed to determine the prevalence of allergic multimorbidity up to age 20 stratified by parental allergies and sex/gender using extensive prospective follow‐up data from two decades of a birth cohort study. Methods In 1990, we recruited 1314 healthy newborns from 6 maternity wards across Germany for the population‐based MAS birth cohort study. The sample was purposely risk‐enriched by increasing the proportion of children at high allergy risk (i.e. at least 2 allergic family members among parents and siblings) from 19% in the source population to 38% in the final sample. The remaining 62% of all MAS children had a low or no allergy risk. Symptoms, medication and doctor's diagnoses of allergic diseases have been assessed using standardized questionnaires including validated ISAAC questions in 19 follow‐up assessments up to age 20. Allergic multimorbidity at each time point was defined as the coexistence of at least 2 of the following diseases in one participant: asthma, allergic rhinitis and eczema. Results Response at age 20 was 72% (n = 942) of all recruited participants. At age 20, 18.5% (95% CI, 15.0–22.5%) of all participants with allergic parents had 2 or 3 concurrent allergies as compared to only 6.3% (95% CI, 4.3–9.0%) of those with non‐allergic parents. At this age, allergic multimorbidity was similar in women and men (12.7% (95% CI, 9.7–16.2%) vs. 11.6% (95% CI, 8.9–14.8%)), whereas single allergic diseases were slightly more common in women than men (24.2% (95% CI, 20.2–28.5%) vs. 20.1% (95% CI, 16.6–24.0%)). Asthma occurred more frequently with coexisting allergic rhinitis and/or eczema than as a single entity from pre‐puberty to adulthood. Conclusion Having parents with allergies is not only a strong predictor to develop any allergy, but it strongly increases the risk of developing allergic multimorbidity. In males and females alike, coexisting allergies were increasingly common throughout adolescence up to adulthood. Particularly asthma occurred in both sexes more frequently with coexisting allergies than as a single entity.